KEMAMPUAN DAYA DUKUNG LINGKUNGAN FISIK DAN PENGARUHNYA TERHADAP KEPUASAN WISATAWAN DI AGROWISATA GREEN HOUSE LEZATTA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Asty, Wina; Wulandari, Dwi Pratitiwi; Anggraini, Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Agro-tourism Green House Lezatta in Agam Regency is known as flower gardens and dollhouses attractions. Based on the observations, tourist attraction has 765 m2, tourist visit rate 600 to 1000 people in the high season, and 500 to 600 people in the low season. The purpose of this study was to determine capacity capability in the physical environment of the Green House Lezatta, whether the quality of the physical environment of a tourist attraction can affect the satisfaction and comfort of tourists visiting. The method used is descriptive quantitative, to assess the maximum capacity of the Green House Lezatta tourist attraction, used the Cifuentes Physical Carrying Capacity (PCC) method. Data obtained through distributing questionnaires to 91 respondents, with the sampling technique using random sampling. The results found carrying capacity of Green House Lezatta's physical environment was not following the standards of a tourist attraction because the number of tourists visiting had exceeded the existing land capacity. In the satisfaction variable, the results showed 49.5% of tourists said not satisfied with the condition of tourist attraction because the atmosphere was uncomfortable and narrow. Recommend to conduct the review of the design of a tourist site following tourism standards for future development.